CENTRAL ASIA IN THE CONTEXT OF THE RUSSIA–UKRAINE CONFLICT: ECONOMIC CONSEQUENCES AND GEOPOLITICAL SHIFTS - Qurbonov Arslonqul Amonovich (Ecominds Press, 2025)
This article examines the economic consequences of the Russia–Ukraine conflict for the countries of Central Asia and the resulting geopolitical transformations in international cooperation. Based on an analysis of the ongoing processes, the paper assesses the role of the Republic of Uzbekistan, whose unique geographical location and pragmatic foreign policy enable it to maintain a position acceptable to all sides. This stance promotes the implementation of comprehensive reforms and contributes to strengthening regional stability amid the formation of a new geopolitical reality.
Keywords: Conflict, political and economic landscape, geopolitical transformation, cooperation, security and stability, sovereignty and independence.